2016
DOI: 10.2967/jnumed.116.174433
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Early Assessment After 1 Cycle of Induction Chemotherapy with 18F-FDG PET/CT and Diffusion-Weighted MRI for Response to Radical Chemoradiotherapy in Head and Neck Squamous Cell Carcinoma

Abstract: The objective of this study was to assess the predictive value of early assessment (after 1 cycle of induction chemotherapy [IC]) with 18 F-FDG PET/CT and diffusion-weighted (DW) MRI for subsequent response to radical chemoradiotherapy in locally advanced head and neck squamous cell carcinoma (HNSCC). Methods: Twenty patients with stage III-IVa HNSCC prospectively underwent 18 F-FDG PET/CT and DW MRI before and 2 wk after each cycle of IC (first cycle, IC1; second cycle, IC2). Response was assessed 3 mo after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 28 publications
1
56
3
3
Order By: Relevance
“…62 In the previously mentioned study of Wong et al, 59 a trend was observed for a higher ADC on DW-MRI after 1 cycle of induction chemotherapy in responders compared with nonresponders of induction chemotherapy followed by concomitant chemoradiation. 59 Conventional DW-MRI cannot separate perfusion and true diffusion-related effect. Intravoxel incoherent motion (IVIM) imaging is characterized by 3 parameters: pure diffusion coefficient; microvascular volume fraction; and perfusion-related incoherent microcirculation.…”
Section: Diffusion-weighted Mrimentioning
confidence: 81%
See 1 more Smart Citation
“…62 In the previously mentioned study of Wong et al, 59 a trend was observed for a higher ADC on DW-MRI after 1 cycle of induction chemotherapy in responders compared with nonresponders of induction chemotherapy followed by concomitant chemoradiation. 59 Conventional DW-MRI cannot separate perfusion and true diffusion-related effect. Intravoxel incoherent motion (IVIM) imaging is characterized by 3 parameters: pure diffusion coefficient; microvascular volume fraction; and perfusion-related incoherent microcirculation.…”
Section: Diffusion-weighted Mrimentioning
confidence: 81%
“…Assessment by PET/CT and DW‐MRI after the first cycle of induction chemotherapy (docetaxel, cisplatin, and 5‐fluorouracil) in 20 patients with advanced‐stage HNSCC who received 2 cycles of induction chemotherapy followed by concomitant chemoradiation was reported by Wong et al Responders, defined as patients without persistent disease at response assessment at 3 months after completion of chemoradiation with MRI, PET/CT, and clinical examination, showed a significantly greater reduction in metabolic tumor volume and total glycolysis both measured for ROI with uptake of ≥40% of SUVmax and with SUV ≥3.5 …”
Section: Introductionmentioning
confidence: 98%
“…The limited number of patients in this study, coupled with the generally favorable PET responses to induction chemotherapy, precluded our ability to detect a correlation between PET changes and long-term oncologic outcomes. In contrast, several prior studies showed that post-induction FDG-PET responses correlated with subsequent PET responses and PFS [28][29][30]. The utility of FLT-PET in assessing responses after induction chemotherapy in HNSCC has only been evaluated by a small number of studies.…”
Section: Discussionmentioning
confidence: 94%
“…These studies have shown that a common pattern is an increase in ADC mean to a varying extent with different therapies. This may occur within days of starting treatment; a higher change in ADC mean is also associated with a pathological good response …”
Section: Validated Mri Biomarkers Requiring Qualificationmentioning
confidence: 99%